Hypercalcaemia Mimicking STEMI on Electrocardiography - Joseph Donovan (Case Reports in Medicine, 2010)
Acute coronary syndrome is a common cause of presentation to hospital. ST segment elevation on an electrocardiogram (ECG) is likely to be cardiac in origin, but in low-risk patients other causes must be ruled out. We describe a case of a man with hypercalcaemia, no evidence of cardiac disease, and ECG changes mimicking acute myocardial infarction. These ECG changes resolved after treatment of the hypercalcaemia.